Analysis of the skin layers and its appendages of developing human fetuses at different trimesters of pregnancy - Kumar Megur Ramakrishna Bhat; FK Febina; Lokadolalu Chandrachar Prasanna (Elsevier, 2025)
Background: Understanding the fundamentals of skin illnesses mediated by the immune system and genetics is aided by knowledge of the composition and structure of fetal skin. In general, the epidermis, skin appendages (including sebaceous glands, hair follicles, and sweat glands), and the underlying dermis from mesenchymal tissue are all derived from the surface ectoderm. Methods: Twelve stillborn or medically terminated human fetuses from the three trimesters of pregnancy (four specimens of different gestational weeks from each trimester) were examined for this study (from January 2024 to June 2024) with institutional ethics committee approval. Histological analysis was performed on skin that was specifically chosen from the flexor (front of the thorax and palm) and extensor (back of the thorax and sole) regions. Results: The epidermis architecture progresses from squamous layered to well-differentiated cellular layers in the third trimester. The cellular dermis with no or very little fibrous component gradually increases with fetal age. As a fetus's gestational age increases, the fibrous material invades epidermal appendages including sweat glands, sebaceous glands, and hair follicles. Conclusion: Appendages of skin and glands begin to appear towards the end of the first trimester. The development of the dermis showed varied differences in the cellular and fibrous components at different trimesters. A fundamental understanding of the formation of the skin in embryos may help regulate the adult wound healing process to promote faster, scar-free healing of the skin and its appendages.